Nut consumption for vascular health and cognitive function. Issue 1 (27th May 2014) - Barbour, Jayne A.; Howe, Peter R. C.; Buckley, Jonathan D.; Bryan, Janet; Coates, Alison M.
Abstract : Nuts are rich in many nutrients that can benefit multiple cardiometabolic functions, including arterial compliance, blood pressure, inflammation, glucoregulation and endothelial vasodilatation. Impaired vasodilatation may contribute to impaired cognitive performance due to poor cerebral perfusion. The present narrative review examines associations between nut consumption, vascular health and cognitive function. It includes a systematic search which identified seventy-one epidemiological or intervention studies in which effects of chronic nut consumption on blood pressure, glucoregulation, endothelial vasodilator function, arterial compliance, inflammatory biomarkers and cognitive performance were evaluated. Weighted mean changes were estimated where data were available; they indicate that nut consumption reduces blood pressure and improves glucoregulation, endothelial vasodilator function and inflammation, whilst a limited number of studies suggest that nut consumption may also improve cognitive performance. Further clinical trials are warranted to explore relationships between nut consumption, endothelial function and cognitive function.